Factors influencing employees’ job motivation: A case study of small and medium logistics enterprises in Vietnam - Kiem, Pham Van; Anh, Nguyen Ngoc; Quynh, Vu Thi Nhu (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this research is to explore the factors influencing employee’s work motivation in Vietnamese SMEs. In the era of globalisation, logistics industry plays an indispensable role and offers significant potential development. However, along with the undeniable development opportunities, small and medium-sized logistics enterprises specializing in providing logistics services are also facing various challenges that stem from market fluctuation, international transporter competition, and other competitive transformations in the digital age. Hence, it is an urgent matter for SMEs and logistics enterprises to attract and retain current skilled staff in order to increase organizations’ productivity and competitiveness since success of the organization depends much upon employees effort and contributions. The author collects and analyzes information from books, newspapers, reports, and publications together with other previous scientific research. These collective data act as the theoretical basis for hypothesis development, questionnaire design, and scale measurements. Based on that, the author gathers data from 332 Vietnamese logistics companies by questionnaire surveys; regression analysis is then used for relationship estimations. The article pointed out five main factors, including employees, leadership, rewards, career promotion, and working conditions that create significant influence on employees’ motivation. The author then suggests various strategies for businesses to boost and improve the motivation of workers in Vietnamese logistics SMEs.